PENGARUH MOTIVASI WISATAWAN TERHADAP DAYA TARIK DALAM MENGUNJUNGI OBJEK WISATA RELIGI KELENTENG SAM POO KONG SEMARANG - Arina Afiyati Shadikah; Risca Ratanasari (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2024)
Religious tourism is one of the developing forms of tourism in Indonesia, including at Sam Poo Kong Temple in Semarang, which holds significant Chinese historical and cultural value. This study aims to analyze the influence of tourist motivation, both intrinsic and extrinsic, on the attractiveness of Sam Poo Kong Temple as a tourism destination. The research employs a quantitative approach using a survey method. A sample of 67 tourists was selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with simple linear regression using SPSS 25. The results indicate that intrinsic motivation significantly influences tourism attractiveness (sig. = 0.000 < 0.05) with a contribution of 72%, while extrinsic motivation also has a significant impact (sig. = 0.000 < 0.05) with a contribution of 28%. Intrinsic factors such as relaxation, self-discovery, and nostalgia have a greater influence compared to extrinsic factors such as novelty and education. This study suggests that management should enhance aspects of attractiveness, such as providing historical information and a variety of souvenirs, to maximize tourist visits. Keywords: Tourist Motivation, Tourism Attractiveness, Religious Tourism, Sam Poo Kong Temple